The Effect of Implicit Preferences on Food Consumption: Moderating Role of Ego Depletion and Impulsivity - Wang, Yan; Zhu, Jinglei; Hu, Yi; Fang, Yuan; Wang, Guosen; Cui, Xianghua; Wang, Lei (Frontiers in Psychology, 2016)
Ego depletion has been found to moderate the effect of implicit preferences on food consumption, such that implicit preferences predict consumption only under a depleted state. The present study tested how trait impulsivity impacts the effect of implicit preferences on food consumption in a depleted condition. Trait impulsivity was measured by means of self-report and a stop signal task. Results showed that both self-reported impulsivity and behavioral impulsivity moderated the ‘depletion and then eating according to implicit preferences’ effect, albeit in different ways. Participants high in self-reported impulsivity and low in behavioral impulsivity were more vulnerable to the effect of depletion on eating. The implications of these results for extant theories are discussed. Future research is needed to verify whether or not trait impulsivity is associated with vulnerability to depletion across different self-control domains.